Examining the Impact of Online Learning Platforms on Undergraduate Academic Performance: Insights from the University of Ilorin - Babalola, Ebenezer; Aina, Deborah Oluwakemi (International Journal of Essential Competencies in Education, 2024)
This study explores the impact of Online Learning Platforms (OLPs) on undergraduate academic performance at the University of Ilorin, Nigeria. Employing a descriptive survey design, the study targeted all undergraduates, with a simple random sampling technique selecting 200 respondents from various faculties. Data were analyzed using descriptive statistics for frequency counts and mean scores, while hypotheses were tested using ANOVA and t-tests at a 0.05 significance level. Key findings revealed that a majority of students (51.9%) did not utilize several available OLPs, reflecting significant gaps in platform integration. Nevertheless, OLPs positively influenced academic performance, with a grand mean score of 3.21, demonstrating enhanced engagement and resource accessibility. Challenges such as inadequate internet connectivity and limited instructor guidance (mean score 3.08) hindered effective utilization. No significant differences were observed in OLP usage across gender (p=0.822) or specialization (p = 0.613), highlighting their inclusivity. The study concludes that OLPs hold considerable potential to improve learning outcomes but require improved integration, infrastructure, and user training to address identified challenges. Recommendations include regular evaluations of platform effectiveness, tailored interventions to meet discipline-specific needs, and investments in digital infrastructure to bridge accessibility gaps. These measures will ensure that OLPs maximize their impact as equitable and effective educational tools.